Influência de uma piscicultura em tanquesrede na dieta e atributos biológicos de Galeocharax knerii na represa de Chavantes, Brasil - Brandão, Heleno [UNESP]; Nobile, André Batista [UNESP]; Souto, Ana Carolina [UNESP]; Ramos, Igor Paiva; de Sousa, Jamile Queiroz [UNESP]; Carvalho, Edmir Daniel [UNESP] (My University, 2013)
The aim of the present study was to evaluate the diet and biological attributes of the population of Galeocharax knerii residing near net cage fish farming activities in the Chavantes reservoir (Paranapanema River, Brazil) to check their possible impacts. Samples were collected from two populations: one near the net cages (NC) and one from an area not influenced by these cages denominated the reference site (RS). Monthly sampling was carried out from March 2008 to February 2009. Fish were caught with a standardized effort using gill nets deployed for 14 hours. The alimentary index (AI) and degree of repletion (RD) were calculated to determine diet composition. Analyses of the sex ratio and the gonadosomatic index (GSI) were also performed. The calculations of AI revealed that fish wastes constituted the most frequent food item in the diet in both study areas (NC = 70.43; RS = 87.55), followed by the consumption of Apareiodon affinis (AI = 29.56), which was abundant near the NC, and prawn at the reference site (AI = 12.28). The sex ratio differed from 1:1 and mature individuals were only found in the population near the NC. The findings demonstrate that G. knerii indirectly benefits from the input of organic matter, using small fish as its main food resource. We conclude that the activities of fish farming influence diet and biological attributes of the species G. knerii, evidenced mainly by higher feeding activity, numerical abundance and biomass in the area of the cages.
Influence of cage fish farming on the diet and biological attributes of Galeocharax knerii in the Chavantes reservoir, Brazil
Keywords: Characidae; Fish; Impact of fish farming; Teleost